Ultrafast spın dynamıcs ın dıluted magnetıc semıconductor nanostructures - Arucu, Muhammet (My University, 2015)
Seyreltilmiş manyetik yarı iletken (DMS) manyetik bir malzemedir, ki o manyetik toprak elementleri ve geçiş metallerin yarı iletken malzemeye katkılanmasıdır. Bu tür yeni nesil elektronik malzemelerde kullanılan DMS malzemeler spin elektroniğinin temelidir. Bu yüzden ferromanyetik yarı iletken malzemeler oda sıcaklığının üstünde Curie sıcaklığına (Tc) sahiptir ve ideal bir spintronik aygıttır. Nobel Ödüllü dev magnetorezistansın (GMR) keşfinden beri, elektronun spini mikroelektronik alanında önemi gittikçe artmaktadır. Hatta kuantum bilgisayarlar spintronik araştırmalarındaki öneminden dolayı, kuantum kriptografi, kuantum iletişim alanlarında spintronik uygulamaların birçok araştırmacı için ilham kaynağı olmuştur. Ancak, DMS oda sıcaklığı ferromanyetizması akademik araştırmalarda hala tartışmalıdır. Bu nedenle, biz bu tezde DMS'lerin manyetik özelliklerini detaylı olarak inceledik. Spintronik olarak bilinen yeni nesil elektronik cihazların sektörünün hızlı gelişmesi eğilimindedir. Bu yeni nesil cihazlar veri aktarım hızı, dijital depolama, güç tüketimi, sensörler, optoelektronik, fotovoltaik gibi özellikler bakımından elektronik agıtlar için önemli avantajlara sahiptir. Bu tür seyreltilmiş manyetik yarı iletkenler yeni bir sınıf Spintronik (Spin + elektronik) malzeme olarak tarif edilmektedir. Bu malzemeler geçiş metali veya toprak grubu elementleri ile katkılandığında farklı manyetik özellikler gösterebililirler. Bu malzemeler periyodik cetvelde II-VI grubunda (ZnO, ...) veya III-V grubunda (GaAs, ...) yer alır. Şimdiye kadar en çok çalışılan DMS malzeme III-V grubu (Ga,Mn)As elementleridir. Daha sonra, (Zn,TM)O materyalleri detaylı olarak incelenmiştir (TM:Mn, Ni, Co). Bu tezdeki amacımız, yukarıda verilen bilgiler ışığında geçiş metalinin (TM) ZnO kristal malzemesine katkılayıp bu malzemenin manyetik özelliklerini inceleyerek yeni teori yöntemler geliştirmek. Bu tezde (Zn,TM)O tabanlı malzemelerin manyetik özellikleri, yeni teknoloji uygulamaları için nanometre boyutlarında malzemeye sıcaklık, manyetik ve lazer atma etkisi altında incelenmiştir. Çalışmamızda Co katkılı ZnO kristali farklı parametrelere göre veya uygulanan harici manyetik alan altında ferromanyetik, paramanyetik, superparamanyetik, antiferromanyetik ve spin camı gibi davranışlar göstermiştir. Bu örnekler x = 0.3 için Zn_{1-x}Co_{x}O sıfır alanda (ZFC) and alanda soğutulmuş (FC) malzeme 20 K civarında sırasıyla spin camı ve süperparamanyetik özellik göstermiştir. Küçük $x$ değerleri için, CoZnO ferromanyetik, büyük x değerleri için ise antiferromanyetik özellik göstermiştir. Bu çalışmada, York Üniversitesi hesaplamalı fizik manyetizma grubu tarafından geliştirilen yüksek performanslı atomistik simulasyon VAMPIRE yazılım paketi kullanıldı. Tez çalışmamızı üç kategoride sınıflandırabiliriz. Çalışmalara başlamadan önce, ilk olarak, ZnO wurtzite kristal yapısının kodu C++ programlama dilinde yazıldı. Daha sonra, Ruderman-Kittel-Kasuya-Yosida (RKKY) etkileşimi kullanarak, atomlar arası değiş tokuş etileşimleri incelendi. İkinci olarak, bu yapılar için, Landau-Lifshitz-Gilbert (LLG) spin hareket denklemi ile Monte Carlo ve Heun yöntemi kullanılarak 5 nm, 10 nm ve 20 nm gibi farklı boyutlarda ve parametrelerde sistemlerin manyetik özelliklerini araştırdık. Üçüncü olarak, farklı Co katkı oranlarında ZnO kristal yapılarına lazer kaynaklarının etkisi incelendi. Son olarak da, sonuçların önemli kısımları yorumlanarak bu çalışmanın sonuçları ve yeni uygulamaları tartışıldı.

A dilute magnetic semiconductor(DMS) is a magnetic material where a part of the host cations are replaced by magnetic ions of rare earths or transition metals. These leads to localized magnetic moments in the semiconductor materials. Therefore DMS is the key materials for spin electronics where not only charge but also spin of electrons are used for electronic devices. Since the discovery of giant magnetoresistance(GMR) resulting of Nobel Prize, the spin of the electron has drawn attention in the field of microelectronics. Although spintronics research lead to quantum computers, quantum cryptography, and quantum communications, closer spintronic applications have inspired many researchers. Ferromagnetic semiconductors with Curie temperature (Tc) above room temperature are ideal as spintronics devices. However, the origin of room temperature ferromagnetism in DMS is still controversial in the literature. In this thesis we examined their feasibility in terms of magnetic properties. New generation of electronic devices known as spintronic has lead to the rapid developing field of industry. These new generation devices have significant advantages over conventional electronics in properties such as speed, digital storage, power consumption, sensors, optoelectronics, photovoltaics. By taking into account the properties of magnetics with that of semiconductors, the new class of materials known as dilute magnetic semiconductors are described as spintronic (spin+electronic) materials. These materials depend on a quantity of transition metal or rare earth atoms which can exhibit different magnetic properties. Generally, these materials is located in II-VI group (ZnO, ...) or III-V group (GaAs, ...) in the periodic table. The most widely studied DMS is (Ga,Mn)As which has been well characterized using standard III-V manufacturing techniques in industry field for further technology. Subsequently, (Zn,TM)O materials were intensively investigated. The goal of this thesis was to develop novel theory methods to understand the properties of transition metal (TM) ions (TM = Mn, Ni, Co) doped ZnO. In this thesis the properties of (Zn,TM)O based systems are studied in relation to the material dimensions, temperature effect, magnetic effect, laser pulse effect in nanometre length scales for new technology applications. Samples of Co doped ZnO crystals showed ferromagnetic, paramagnetic, superparamagnetic, antiferromagnetic and spin glass behaviour with the magnetic element doped and different external magnetic field. Zero field cooled (ZFC) and field cooled magnetization displaying around 20 K at a blocking temperature. Magnetic properties of the Co doped ZnO samples were found at different anisotropy value along the different crystallographic axes and different external applied field. Zn_{1-x}Co_{x}O samples for x = 0.3 show superparamagnetic and spin glass behaviour at temperatures around 20 K respectively. The measured magnetization of these samples was proportional the Co content in the samples. For small x values, CoZnO ferromagnetic, for large values of x showed the antiferromagnetic properties. In the our studies was used VAMPIRE software package for magnetic properties which is high performance code, developed by The University of York, Department of Physics Computational Magnetism Group for our investigations. Vampire is a free, open source software package which makes atomistic simulations of magnetic materials available to both theoretical and experimental researchers. We can classify into three categories the these studies. Firstly, we created ZnO wurtzite crystal structure writing C++ code. Later, using Ruderman-Kittel-Kasuya-Yosida (RKKY) interaction we obtained the nearest neighbour interaction of ZnO that this have different sizes like 5 nm, 10 nm and 20 nm. Secondly, for these structures, we investigated the magnetic properties of these systems using Monte Carlo Method and Heun Method described by the Landau-Lifshitz-Gilbert(LLG) equation which the equation of motion for spins. Thirdly, we researched laser induced spin dynamics for the different Co doped ZnO crystal structures. Finally, a summary and a short outlook is given the of most important results and discuss some new applications or questions arising from the conclusions of this work.
Keywords: Fizik